2019
DOI: 10.21512/bbr.v10i1.5407
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationship between Social Benefit, Dependency, Satisfaction, and Habit Formation on the Use of Social Media

Abstract: The main objective of the research was to investigate whether a consumers’ habit formation was influenced by the satisfaction they got because of the social benefit and dependency on the use of social media. The research design used survey methods with questionnaires for 100 respondents. The researchers employed Structural Equation Models (SEM) with AMOS software to test the research model. From consumer’s profiles, the results show that the most widely used types of social media are Line and Instagram. Most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to research results, individuals use online social platforms for more than 3 hours a day and can get their basic and social needs both from here. Social media addiction levels of the participants were found to be high, but it was found that this turned into a habit that creates a sense of satisfaction for both genders (Santoso & Oetomo, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…According to research results, individuals use online social platforms for more than 3 hours a day and can get their basic and social needs both from here. Social media addiction levels of the participants were found to be high, but it was found that this turned into a habit that creates a sense of satisfaction for both genders (Santoso & Oetomo, 2019).…”
Section: Discussionmentioning
confidence: 96%